COMPARATIVE STUDY OF TWO HELIX ASPERSA EXTRACTS ON TUMOR CELL LINES (HUT-78 AND SEAX) PROLIFERATION AND MMP-9 SECRETION - Romeila, Mebirouk; Dalila, Naimi; Meriem, Riani; Frank, Antonicelli (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Despite the progress in cancer research, current therapies are ineffective and cause many adverse effects. The discovery of new natural anti-tumor agents that can act on multiple mechanisms of growth and tumor invasion with minor side effects and which can be safe for patients. Therefore, we sought new natural products from an invertebrate organism belonging to the phylum of mollusks: a land snail, Helix aspersa. This study was aimed to evaluate the cytotoxic activity of two extracts prepared from Helix aspersa, on two cutaneous T cell lymphoma cell line (HUT-78 and SeAx). Their effect on MMP-9 expression was also tested. Methods: We prepared from the snail Helix aspersa: an aqueous (AE) and a hydroalcoholic extracts (HAE). We have evaluated the concentration of total proteins and total phenols in these extracts. The percentage of cell mortality was evaluated after incubating the cell lines with the two extracts at different concentrations, by using trypan blue exclusion method. Finally, the tumor cells expression of metalloproteinase MMP-9 was examined by zymography analysis. Results: We have found that 1 mg/ml of AE contains (4.53±0.48 mg) of total proteins and (2.44±0.11 mg) GAE g-1of phenols. 1 mg/ml of HAE contains (1.83±0.23 mg) of total proteins and (2.81±0.16 mg) GAE g-1 of phenols. On one hand, both extracts exerted a toxic effect on these tumor cells. Indeed, aqueous extract induced 44.09 % mortality in HUT-78 and 31.47 % mortality in SeAx tumor cell line with 50 µg/ml. While, the hydroalcoholic extract induced 29.90 % in HUT-78 and 25 % in SeAx. On the other hand, the result showed no changes of MMP-9 expression. Conclusion: Helix aspersa's extracts had a toxic effect on cutaneous T cell lymphoma (CTCL), but did not inhibit the production of the protease by these two cell lines in culture.